Survey on Cloud Based Robotics Architecture, Challenges and Applications - Shakya, Subarna (Journal of Ubiquitous Computing and Communication Technologies, 2020)
The emergence of the cloud computing, and the other advanced technologies has made possible the extension of the computing and the data distribution competencies of the robotics that are networked by developing an cloud based robotic architecture by utilizing both the centralized and decentralized cloud that is manages the machine to cloud and the machine to machine communication respectively. The incorporation of the robotic system with the cloud makes probable the designing of the cost effective robotic architecture that enjoys the enhanced efficiency and a heightened real- time performance. This cloud based robotics designed by amalgamation of robotics and the cloud technologies empowers the web enabled robots to access the services of cloud on the fly. The paper is a survey about the cloud based robotic architecture, explaining the forces that necessitate the robotics merged with the cloud, its application and the major concerns and the challenges endured in the robotics that is integrated with the cloud. The paper scopes to provide a detailed study on the changes influenced by the cloud computing over the industrial robots.
Keywords: Robotics; Cloud Computing; Cloud Based Robotics; Big Data; Internet of Things; Open Source; Challenges and Applications